Função logarítmica : uma nova abordagem para o ensino médio - Silva Filho, Sinésio Mateus da (2015)
In order to overcome the difficulties of teaching and learning the logarithmic function, we present in this paper a more accessible teaching sequence, so that teachers can apply it to their students, thus creating an interesting option to the traditional way usually used by schools. To prepare this teaching sequence, we chose to introduce and present the theory of logarithmic function in context, using historical, geometric and algebraic arguments. Through these tools we aim to build an educational proposal in which learning is meaningful to the student